L’apprentissage de la rhétorique au regard de la papyrologie : études de cas - Sans, Benoît; Vanthieghem, Naïm (Rivista Italiana di Filosofia del Linguaggio, 1970)
This article proposes reflection on the contribution of papyrology to our knowledge of the education system in Greco-Roman Egypt, with a particular attention for the teaching of rhetoric. It first provides an overview of the education system, and then focuses on the teaching of rhetoric through the analysis of recently published papyrus. These rhetorical training evidences provide precious and more practical complementary information to the theoretical treatises.